Pengembangan Video Berbasis Pendekatan Deep Learning Untuk Meningkatkan Kemampuan Pemecahan Masalah Pada Pembelajaran IPAS di SD - Sumardi; Firman Catur Wibowo; Indra Jaya (Prosiding, 2025)
21st-century education demands that students adapt to rapid social, economic, and technological change. The Independent Curriculum (Curriculum Merdeka) is designed as a strategy to equip students with essential material, 21st-century skills, and strong character development. One of the main obstacles to learning Natural and Social Sciences (IPAS) in elementary schools is students' low problem-solving abilities, as shown by the results of the PISA 2022 international survey. Innovation in learning media is needed, one of which is through the development of videos based on a deep learning approach that can deepen conceptual understanding, support contextual learning, and train higher-order thinking skills. This study aims to develop a deep learning-based learning video to improve students' problem-solving skills in the IPAS subject. The research method uses the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. A trial was conducted on sixth-grade students of SDN Karang Satria 04, Bekasi Regency, using needs questionnaires, expert validation, and problem-solving tests. The results showed that the media was deemed "very valid" and "practical," with 95% of students interested in learning IPAS through videos. Effectiveness tests showed a significant increase in problem-solving abilities, particularly problem identification, hypothesis formulation, and solution determination.